Transcatheter Aortic Valve Implantation in Two High-Risk Patients with Low Coronary Ostial Heights Using the Novel Balloon-Expandable Myval Valve - N, Raja Ramesh; Daggubati, Ramesh; P, Ramesh Babu (Journal of Cardiology and Cardiovascular Medicine, 2023)
The treatment of severe aortic stenosis by transcatheter aortic valve implantation (TAVI) is challenging in patients with high-risk coronary anatomy that is predisposed to iatrogenic or delayed coronary obstruction. Hence, the evidence on performing TAVI with adequate coronary protection with or without deploying a stent needs to be accumulated. We report two cases of TAVI performed in patients with low coronary heights, wherein a “wire only” strategy was used to provide coronary protection along with the implantation of a novel balloon-expandable Myval THV. The first patient underwent a valve-in-valve TAVI, while the second patient underwent the replacement of a native bicuspid Type 1A valve. This case series presents two high-risk TAVI cases wherein a guide extension catheter and a supportive coronary guidewire provided sufficient coronary protection. None of the cases required any rescue revascularization and no incidences of a new pacemaker implantation were reported.